2019
DOI: 10.1111/josh.12757
|View full text |Cite
|
Sign up to set email alerts
|

State Physical Education Policy Changes From 2001 to 2016

Abstract: BACKGROUND: State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report. METHODS:Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
(38 reference statements)
0
15
0
1
Order By: Relevance
“…Research has showed that physical education teachers hold different views on assessment, and they acknowledge that there is a need to change involving students in the process Bores-García et al, 2021;Bores-García et al, 2020). Unfortunately, within the close structure of national curriculums, the idea of using assessment as a learning tool is very limited (Dauenhauer et al, 2019). A recent review on assessment and learning standards (cognitive, motor and socio-affective) included in the physical education curriculum in Spain in Primary Education (Otero-Saborido et al, 2020) found that the dominant was the cognitive (39.42%), followed by the motor (30.94%), and the socio-affective (29.65%).…”
Section: Assessment Approaches In Physical Educationmentioning
confidence: 99%
“…Research has showed that physical education teachers hold different views on assessment, and they acknowledge that there is a need to change involving students in the process Bores-García et al, 2021;Bores-García et al, 2020). Unfortunately, within the close structure of national curriculums, the idea of using assessment as a learning tool is very limited (Dauenhauer et al, 2019). A recent review on assessment and learning standards (cognitive, motor and socio-affective) included in the physical education curriculum in Spain in Primary Education (Otero-Saborido et al, 2020) found that the dominant was the cognitive (39.42%), followed by the motor (30.94%), and the socio-affective (29.65%).…”
Section: Assessment Approaches In Physical Educationmentioning
confidence: 99%
“…Noticeably, both China and Russia have required HRF component fitness testing for each year from K-16 (Keating et al, 2018; Liu et al, 2017), while most Western countries such as the US, UK, Canada, and Australia test only K-12 students, and allow teachers the option to choose how and when throughout the student’s academic career to test (Cale et al, 2014; Garrett and Wrench, 2008; Keating, 2003; Phillips et al, 2017; Silverman et al, 2008). It is important to note that some states in the US, such as California and Texas, mandate yearly youth fitness testing (Dauenhauer et al, 2019; Morrow et al, 2009). One important aspect found was that most countries were seen to periodically revise and maintain their testing batteries in order to improve the fitness tests’ effectiveness and utilize current testing knowledge on youth fitness testing in schools (Keating et al, 2019; Liu et al, 2017; Pate et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of researchers have suggested abandoning youth fitness testing (Cale et al, 2007; Corbin et al, 1995; Harris and Cale, 2006; Lloyd et al, 2003; Rowland, 1995). Nevertheless, empirical data have suggested that youth HRF testing continues in school-based PE programmes worldwide (Alfrey and Gard, 2019; Castro-Piñero et al, 2010; Cohen et al, 2015; Dauenhauer et al, 2019; Keating et al, 2018; Morrow et al, 2009). Thus, there is a need for more research on the topic, considering that previous studies have suggested that fitness testing can be either beneficial or harmful, depending on how it is used (Cale et al, 2014; Ernst et al, 2006; Mauch et al, 2017; Silverman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…15,23,24 Those who argue in favor of continuing to deploy school-based PFT contend that it is imperative to monitor the epidemiology of youth fitness because of the very robust evidence regarding the beneficial health aspects of fitness and the importance of attaching some measure of accountability to physical education (PE) programs. 17,25 Moreover, in the absence of school-level data, disparities in youth fitness across school districts, communities, and states may go un-noticed and therefore unaddressed. In a perhaps unique example of the data from PFT being used to inform policy, reporting of fitness survey results led to statewide funding to pay for licensed PE teachers in California elementary schools.…”
mentioning
confidence: 99%